2002
DOI: 10.1051/agro:2002044
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilizer value of cattle manure applied on soils originating from organic and conventional farming systems

Abstract: International audienceNitrogen nutrition of plants in organic farming depends largely on animal manure. In a pot experiment the hypothesis was tested that on a long-term organically managed soil (ORG) characterized by higher soil microbial activity, a greater portion of N applied as cattle manure is mineralized and taken up by plants than on a conventionally managed soil that had received exclusively mineral fertilizers (MIN). Dry matter yields and N uptake by Italian ryegrass were higher by around 20% on ORG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 28 publications
6
42
2
Order By: Relevance
“…Th is result was consistent with those of Hadas et al (1996), who found that within a period of 32 wk, net N mineralization from cattle manure was not higher in soils with long-term use of cattle manure amendments compared with soils that had not been amended for 30 yr. Th ey argued that the decomposition of recently added organic matter may be independent of the initial soil microbial biomass and activity. Similarly, Langmeier et al (2002) found no consistent eff ect of fertilization history (organic vs. conventional) on plant N uptake from recently added cattle feces and slurry, although the soils used diff ered greatly in soil microbial biomass. In both studies, diff erences in net N mineralization were mostly due to diff erences in N mineralization from previously existing SOM.…”
Section: Effects Of Amendment History On Decomposition Of Recently Admentioning
confidence: 93%
See 1 more Smart Citation
“…Th is result was consistent with those of Hadas et al (1996), who found that within a period of 32 wk, net N mineralization from cattle manure was not higher in soils with long-term use of cattle manure amendments compared with soils that had not been amended for 30 yr. Th ey argued that the decomposition of recently added organic matter may be independent of the initial soil microbial biomass and activity. Similarly, Langmeier et al (2002) found no consistent eff ect of fertilization history (organic vs. conventional) on plant N uptake from recently added cattle feces and slurry, although the soils used diff ered greatly in soil microbial biomass. In both studies, diff erences in net N mineralization were mostly due to diff erences in N mineralization from previously existing SOM.…”
Section: Effects Of Amendment History On Decomposition Of Recently Admentioning
confidence: 93%
“…While many studies confi rm the concept that amendment history eff ects on the decomposition of recently applied amendments can be neglected (Fauci and Dick, 1994;Hadas et al, 1996;Langmeier et al, 2002;Stark et al, 2008), some do not. For example, Fließbach et al (2000) reported higher C mineralization from recently added straw in "biodynamically" managed soil compared with conventionally managed soil (unamended, mineral fertilization, or mineral + organic fertilization).…”
mentioning
confidence: 99%
“…The rationale behind this is that the MB, microbial community structure and microbial activity of soil adjust quickly to newly added organic matter, so that initial properties of the soil microflora can be ignored in the prediction of short-term N mineralization from organic fertilizer. Most published studies on this issue support this theory (e.g., Fauci and Dick, 1994;Hadas et al 1996;Langmeier et al 2002;Stark et al 2008), although others have found an effect of long-term fertilization history on C mineralization (Fliessbach et al 2000) or N mineralization (Mallory and Griffin 2007) from newly added organic matter.…”
Section: Introductionmentioning
confidence: 97%
“…Organic farming methods tend to increase soil organic matter and thus enhance soil fertility (Langmeier et al, 2002;Mäder et al, 2002), making it less dependent on external inputs. Organic farming may also provide ecosystem services, increase biodiversity and have a positive impact on the landscape (Letourneau and Bothwell, 2008;Norton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%